Organotin(IV) Carboxylates of Substituted α‐Cinnamic Acid, RnSn(OCOC(R2)=CHR1)4 –n: Synthesis, Spectroscopic Characterization and Biological Evaluation. Issue 6 (19th June 2015) - Sadiq‐ur‐Rehman,; Khan, Bilal Ahmad; Chaudhary, Muhammad Aziz; Yasin, Khawaja Ansar; Ali, Saqib
ABSTRACT: Di‐ and triorganotin(IV) carboxylates, R n Sn(OCOC(R 2 )=CHR 1 )4–n ( n = 2 and 3; R = Me, Et, n ‐Bu, Ph; R 1 = 3‐CH3 O‐4‐OHC6 H3, R 2 = C6 H5 ) were prepared by reacting the corresponding organotin(IV) chloride with the silver salt of the ( E )‐3‐(4‐hydroxy‐3‐methoxyphenyl)‐2‐phenylpropenoic acid. The title compounds were investigated and characterized by elemental analysis, infrared (FT‐IR), multinuclear ( 1 H, 13 C, 119 Sn) NMR, and mass spectrometry, and possible structures were proposed. The complexes and ligand acid (HL ) have been evaluated in vitro against various bacteria and fungi. The results noticed during the biocidal activity screenings proved their in vitro biological potential. They were also tested for cytotoxicity.